Features of Psychological Defenses and Coping Strategies among Teachers of Preschool Educational Institutions with Different Levels of Psychological Well-being - E.V. Vorobyeva; L.R. Pravdina; A.V. Shevchenko (Moscow State University of Psychology and Education, 2024)
The aim of the work was to identify the features of psychological defenses and coping strategies among teachers of preschool educational institutions with different levels of psychological well-being. The study involved 62 educators of preschool educational institutions in the city of Rostov-on-Don, the city of Aksai and the village of Rassvet, Rostov Region. The following methods were used: “Scale of psychological well-being” by K. Riff, technique for measuring psychological defense by E.R. Pilyugina, R.F. Suleimanov, questionnaire “Types of orientations in difficult situations” by E.V. Bityutskaya, A.A. Korneeva. As a result of the study, it was found that teachers with a high level of psychological well-being more often use adaptive psychological defenses, teachers with an average level of psychological well-being more often use psychological defense of the infantile type, teachers with a low level of psychological well-being more often use psychological defense of the psychotic, as well as infantile and neurotic types. Teachers of preschool educational institutions with a high level of psychological well-being are distinguished by their preference for coping strategies related to the type “Orientation towards rapprochement, interaction with difficulty.” Teachers of preschool educational institutions with an average and, especially, a low level of psychological well-being tend to be more inclined to use coping strategies related to the type “Orientation towards leaving and moving away from difficulties.” It is recommended to use the results of the study in psychoprophylactic and psychocorrective work with preschool teachers.